Second Language and background language influences on the oral production of Spanish words and phrases as a third language among 5-6 year old students - Norely, Abd Rahman (2017)
This study aimed to discover the possible factors that contribute to the oral production of words and phrases among 5-6 year old kindergarten students learning Spanish as third language in an international school in Kuala Lumpur, Malaysia. Six subjects were involved in the study with three different mother tongues; namely, of Chinese, Hindi and Indonesian language (Bahasa Indonesia) and English was the medium of instruction in school. The study was conducted over a period of one school year and specifically examined the role of English proficiency (L2) in the production of English-Spanish cognates, the role of mother tongue (L1) and crosslinguistic awareness in the production of Spanish words and phrases. Also examined were the influence of parental support and role of songs on the oral production Spanish words and phrases. Data was collected through in-depth interviews with the young subjects and observations of Spanish teaching-learning sessions which were videotaped. Questionnaire were passed on to parents followed by telephone interviews to corroborate information about the home environment of subjects, types and frequency of support. An interview was also conducted with the Spanish teacher to obtain a more in-depth understanding of the behaviours of subjects during class sessions. The results of the study showed that among the different mother tongues, subjects with Hindi as their mother tongue (L1) produced the most number of Spanish words and phrases which may be attributed to Spanish and Hindi originating from the same language branch. In terms of the English-Spanish cognates that were produced, generally subjects who were proficient in English (L2) produced more cognates compared to subjects who were less proficient (based on WIDA scores) with the exception of one subject. Also, subjects were able to produce more Spanish phrases and words that were introduced using songs. Subjects who demonstrated cross-linguistic awareness, especially in terms of awareness of the similarities between learning English and Spanish produced more Spanish words and phrases. However, parental support and support outside the class did not influence the production of Spanish words and phrases. The findings of the study support the Typological Primacy Model, L2 Status Factor, Developmentally Moderated Transfer Hypothesis and Cumulative Enhancement Model to a certain degree. Exposing children to a third language at such a young age is a valuable endeavor. It is proven that younger students can learn multiple languages at one time when given the opportunity.